Facing adversity: the socio-economic and cultural barriers encountered by hindu migrant taxi drivers in Saudi Arabia - Singh, Amrendra Kumar; Majhi, Tulasi Das (Studia Etnologiczne i Antropologiczne, 2024)
This paper examines the socio-economic and cultural challenges faced by Hindu migrant taxi drivers in Saudi Arabia, focusing on the interplay between economic vulnerability, cultural isolation, and resilience. Based on longitudinal ethnographic research, it highlights how the kafala system, high recruitment fees, long hours, and restricted religious practice deepen precarity, while community networks and adaptive strategies enable drivers to persist despite systemic neglect and pandemic-related hardships.